PREVALENCE AND IMPACT OF PAINFUL DIABETIC PERIPHERAL NEUROPATHY IN PATIENTS WITH TYPE-2 DIABETES MELLITUS WITH LOW ECONOMIC STATUS - Chowdary Dl, Nishitha; I, Somasundaram (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the study were to study the prevalence of painful diabetic peripheral neuropathy (PDPN) in patients with type-2 diabetes and to access the health-related quality of life of patient by collecting and documenting the information of patient using sf-15 questionnaire. Methods: The present study involves prospective analysis of quality of life in both men and women with PDPN with type-2 diabetes. The methodology involves collection and documentation of patients medical and medication history, blood glucose levels, and duration of diabetes. Further, the quality of life of patient is documented using Michigan neuropathic scaling instrument (sf-15 questionnaire) through which we can assess the impact of PDPN. Results: It can be seen that there are no significant changes in the prevalence of PDPN when compared gender wise and based on age, but there are an extremely statistically significant (*p<0.05) values obtained when the presence of PDPN is compared between duration of diabetes. Conclusion: Patients with duration of diabetes type-2 between 5 and 10 years are mostly presented with PDPN. Early detection, nutritious diet, and patient counseling help in management of PDPN.